The Bahamas : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for The Bahamas. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2021)
The economic impact of COVID-19 on The Bahamas is unprecedented. The archipelago was just recovering from the devastation of Hurricane Dorian in the fall of 2019, when the pandemic led to a sudden stop in tourism, the main source of income and employment. The authorities mounted a rapid emergency response to support the economy and vulnerable households and put in place strict containment measures. But amid limited testing and health resources, reopening the economy has been challenging.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet